Work Life Balance and Self Control with the Performance of Police Investigators at the Central Kalimantan Regional Police - Faujiah, Faujiah; Noviekayati, Noviekayati; Pratitis, Niken Titi (Formosa Journal of Multidisciplinary Research, 2024)
When police work over a given time period is compared to different options, such as predetermined and mutually agreed-upon standards, targets, or criteria, the outcome is police performance. The performance of the National Police in enforcing the law in Indonesia still needs to be improved or improved. Based on E-Investigation Management in 2024, the total crime trend cases in 2024 reached 4,436 cases, with theft still being the most frequently occurring type of crime. The lack of work life balance and self-control could trigger the low performance of the National Police in several previous studies. Researchers researched 148 subjects, based on the results of analysis with Kendall Tau B, it showed that there was a very significant relationship between the work-life balance variable and performance. This means there is a significant positive relationship between work-life balance and the performance of investigators at the Central Kalimantan Regional Police. Then, self-control and performance showed that there was a very significant relationship between self-control and performance. This means that there is a very significant positive relationship between self-control and the performance of investigators at the Central Kalimantan Regional Police.